2006
DOI: 10.1093/aob/mcl031
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal Oscillations in Orange Trees under Natural Climatic Conditions

Abstract: The results show marked stomatal oscillations persisting under natural climatic conditions and underscore the need to discover why this phenomenon is so pronounced in orange trees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…Burgess et al 1998;Howard et al 1996;Hultine et al 2004;Lott et al 1996;Meinzer et al 2004a;Nadezhdina and Cermak 2003;Oliveira et al 2005;Sakuratani et al 1999;Smith et al 1999) and branches (e.g. Alarcon et al 2003;Chapotin et al 2006;Fernandez et al 2006;Hubbard et al 2002;Martin et al 2001;Meinzer et al 2004b;Phillips et al 1999;Steinberg et al 1990;Steppe et al 2006;Yonemoto et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Burgess et al 1998;Howard et al 1996;Hultine et al 2004;Lott et al 1996;Meinzer et al 2004a;Nadezhdina and Cermak 2003;Oliveira et al 2005;Sakuratani et al 1999;Smith et al 1999) and branches (e.g. Alarcon et al 2003;Chapotin et al 2006;Fernandez et al 2006;Hubbard et al 2002;Martin et al 2001;Meinzer et al 2004b;Phillips et al 1999;Steinberg et al 1990;Steppe et al 2006;Yonemoto et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The period of the g s oscillations that have been observed in some of our measurements (Fig. 1) is much shorter than the period of oscillations that are primarily controlled by plant water status (Barrs 1971, Steppe et al 2006. A pattern of measured g s was more scattered in plants exposed to low VPD, which indicates that stomatal response could be more synchronous under higher VPD, as suggested by Kaiser and Kappen (2001).…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, the hydraulic connectivity between the soil water reservoir and the plant water pathway relies on a negative water potential gradient created by leaves water transpiration. For comprehensively investigating the plant-water relation, various sensing techniques have been developed, such as those for leaf stomatal conductance (Friend et al, 1989;Steppe et al, 2006;Blonquist et al, 2009), leaf water potential (Turner and Long, 1980;Zimmermann et al, 2008), leaf temperature (Hashimoto et al, 1984;Rahkonen and Jokela, 2003;Gontia and Tiwari, 2008), leaf thickness (Li et al, 2009;Seelig et al, 2012), stem water potential (Choné et al, 2001;Yang et al, 2012), stem diameter variation (Fernández and Cuevas, 2010), stem sap flow rate (Č ermák et al, 1973;Bakfr and Van Bavel, 1987;Smith and Allen, 1996;Trcala and Č ermák, 2012), stem water content (Wullschleger et al, 1990;Irvine and Grace, 1997) and root water potential/pressure (Fiscus, 1972;De Swaef et al, 2013). However, even though these sensors provide different physiological information to support insights into plant water status, none provides a single measure that is well correlated with the numerous factors influencing plant water stress (Kramer, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…The water flow upward through plant is related to both the long-distance transport in xylem conduits and local dynamic exchange of the water between the xylem conduits and the storage tissues (Steppe et al, 2006;Sevanto et al, 2011). Many studies for trees observed a time lag between leaf transpiration response and stem sap flow response, varying from minutes to hours once solar radiation induces transpiration activity (Schulze et al, 1985;Goldstein et al, 1998;Steppe et al, 2002;Scholz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%